Enabling dynamic spectrum access using SS-MC-CDMA - DOYLE, LINDA; NOLAN, KEITH EDWARD; SARATH, DEEPAK; SUTTON, PAUL DAVID (IEEE, 2007)
The demand for frequency spectrum and diversity of wireless devices accessing this spectrum depends upon the time of day, the characteristics of a frequency band, and the geographical location of the observer/wireless device. This paper highlights the value of employing a novel dynamic spectrum access technology using a highly reconfigurable spectrum access scheme with excellent frequency diversity properties. We name this robust scheme selective subcarrier multi-carrier code division multiple access (SS-MC-CDMA). This paper contains three main contributions. Firstly, the reconfigurability options in a physical layer (PHY) using MC-CDMA and the flexibility in system design of a cognitive radio are presented. Secondly, an application of the novel SS-MC-CDMA system in a dynamic spectrum access (DSA) scenario is developed in order to indicate the value and potential of this system. Finally, based on this scenario, we present some initial key results from both simulation and real-world experiments.
Proceedings of the 2nd International Conference on Cognitive Radio Oriented Wireless Networks and Communications
2nd International Conference on Cognitive Radio Oriented Wireless Networks and Communications, CrownCom
PUBLISHED
Orlando, FL, USA
Keywords: Electronic & Electrical Engineering